Pendampingan Keterampilan Menyimak Cerita Berbahasa Inggris Dengan Metode Story Telling Di Mi Nurul Huda Sukaraja - Puji, Puji Adi Pertiwi; Fitriani, Herni; Mufidah, Aqlin Naila Rosydatul (Universitas KH. Mukhtar Syafaat (UIMSYA), 2025)
Listening is a learning process carried out by students to carry out listening activities, understand, evaluate and respond to what has been heard. Listening skills are receptive language skills because in this skill the meaning of language is obtained and processed through symbols and verbally. Based on what will be done in this community service activity, the listening skills of English stories in grade V students at MI Nurul Huda Sukaraja school are still focused on mastering grammar and vocabulary structure which is done through Drilling Activities and the low ability and interest in listening to a story using the story telling method. In this service, several problems were found in listening skills, namely (1) the implementation of the English listening skills process is still focused on the teacher (Teacher Center Learning), 2) Students are busy with their friends and often play, (3) there is no interaction between teachers when given a question because students have not mastered the material and have not understood it, and (4) students are not interested and not enthusiastic during the learning process. It can be concluded from this listening that many failures in the learning process occur because the teacher and students do not understand or the teacher has not provided an understanding of how to listen well and correctly and that listening skills are needed as a basis for improving learning. The purpose of this community service activity focuses on skills and applying students in listening to English stories using the story telling method in English learning. The desired result is to improve English story listening skills using the story telling method in English learning properly according to the material provided, students are very enthusiastic in this service and enjoy this listening skills material. based on the results of the mentoring and the diagram, it can be described that 85% of students listened to the English story (18 students listened and 3 did not listen from a total of 21 students), then 87% of students understood the English story and 40% of students did not understand the English story (16 students understood and 5 students did not understand from a total of 21 students), if all aspects of the mentoring in listening to the story are added up, the average score is 70% seen from these results, the mentoring in listening to English stories with the storytelling method at MI Nurul Huda has increased from these results, it is included in the criteria for students to understand listening to English stories with the storytelling method, especially in the digital era, many use gadgets where students often use games to play rather than listening to English stories with the storytelling method.